2020
DOI: 10.1017/s0022029920001089
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phytanic acid-induced changes in tissue fatty acid profiles in mice

Abstract: The aims of this research communication were to investigate the in vivo tissue accumulation of phytanic acid (PA) and any changes in the tissue fatty acid profiles in mice. Previous in vitro studies have demonstrated that PA is a milk component with the potential to cause both beneficial effects on lipid and glucose metabolism and detrimental effects on neuronal cells. However, there is limited information about its in vivo actions. In this study, mice were fed diets containing either 0.00 or 0.05% 3RS, 7R, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Our previous study has shown that nPA can be detected in the mouse body when fed a diet containing 0.1% nPA for 4 weeks. [ 16 ] In the current study, a 0.05% intake group was established in addition to the 0.1% group to investigate the intake‐dependency in the anti‐inflammatory effects of nPA. However, the two diets showed different efficacies depending on the endpoint selected and no clear intake‐dependence effect was found between the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has shown that nPA can be detected in the mouse body when fed a diet containing 0.1% nPA for 4 weeks. [ 16 ] In the current study, a 0.05% intake group was established in addition to the 0.1% group to investigate the intake‐dependency in the anti‐inflammatory effects of nPA. However, the two diets showed different efficacies depending on the endpoint selected and no clear intake‐dependence effect was found between the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that the above studies investigating functional properties of phytanic acid have been limited to in vitro cell‐based models. Apart from our previous investigation into the issue accumulation of orally administered phytanic acid in mice, [ 16 ] there have been no reports evaluating health‐promoting effects of phytanic acid at the in vivo level. Further in vivo investigation using animal models of human disease will be required to determine the practical efficacy of phytanic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pioglitazone selectively lowered the enrichment of the proinflammatory omega-6 lipid arachidonic acid in adipose cell membranes, without altering levels of omega-3 docosahexaenoic acid, providing a novel mechanistic link between adipose expandability and systemic inflammation. Whether prospective natural ligands of PPARγ, such as branched chain fatty acids [ 163 ], represent a useful nutritional approach to combat visceral adiposity, especially in MUO phenotypes, requires further study.…”
Section: Precision Nutrition To Compliment Adjunct Pharmacotherapiesmentioning
confidence: 99%